(untitled) (Revista Española de Derecho Internacional, 2008)
Blackwater is an outstanding civilian staffed American corporation that provides military services under contract to the US Government. Some killings and incidents highlight the challenge of regulating these contractors. Well-established rules of international law apply to States in their relations with private military and security companies. States retain their obligations on the use of force when they contract military services. The UN Security Council should have a say on this subject-matter. This contribution prioritizes the item concerning accountability of private security contractors, namely Blackwater acting in Iraq and Afghanistan, under international and domestic law. Some Blackwater actions have been subject to the US jurisdiction. McMahon v. Presidential Airways Inc. illustrates the point on whether subjecting a contractor to liability under state tort law would create a significant conflict with Government’s interests. The legal path is not easy, but there are options.